Does Q223R Polymorphism of Leptin Receptor Influence on Anthropometric Parameters and Bone Density in Childhood Cancer Survivors? - Malgorzata Sawicka-Żukowska; Maryna Krawczuk-Rybak; Katarzyna Muszynska-Roslan; Anna Panasiuk; Eryk Latoch; Jerzy Konstantynowicz (International Journal of Endocrinology)
Childhood cancer survivors are in augmented risk for developing obesity. For many factors leptin and leptin receptor gene polymorphism play an important role in the development and metabolism not only of fat, but also, bone tissue. The aim of the analysis was to find the relationships between Q223R, leptin levels, and anthropometric parameters. Patients and Methods. In the study 74 cancer survivors participated (ALL n=64, lymphomas n=10), and the control group consisted of 51 healthy peers. Leptin blood concentration was determined by ELISA method. To estimate leptin receptor gene polymorphism, RFLP method was used. Bone mineral density (BMD) and content (BMC), fat, and lean tissue measurements were obtained by DXA. Results. We found no correlations between serum leptin concentrations and anthropometric parameters nor BMD. Serum leptin concentrations were significantly lower in the group of cancer survivors compared to controls; however, in those overweight from examined group we found leptin levels higher than those in nonoverweight. Genotype Q223R was not associated with higher leptin levels, BMI, BMD, body fat or lean tissue. Conclusion. To our knowledge, this is the first report describing the relationship between BMD and Q223R polymorphism in childhood cancer survivors. Further analysis, based on a larger group of patients, is needed to confirm these findings.